Skład pokarmu orlika krzykliwego Clanga pomarina na terenie Magurskiego Parku Narodowego - Paradysz, Jan; Kiec-Paradysz, Aneta (Leśne Prace Badawcze, 2024)
In 2020–2021, the diet of the Lesser Spotted Eagle ( Clanga pomarina ) was studied in the central part of the Magura National Park in southern Poland. The diet composition was determined by analyzing pellets and prey remains under occupied nests. Of the 92 prey items collected, the diet, measured by biomass, consisted of 32.12% reptiles, 66.88% mammals, 0.75% amphibians and 0.25% insects. The main mammalian prey taxa were members of the family Cricetidae , while the most commonly eaten insects were from the family Carabidae . Insects were the second numerically most important prey category with 18.48%.